Analisis Pengelolaan Perkampungan Adat Dengan Konsep Community Based Tourism Di Kabupaten Sijunjung - Sevia Nurfaizah; Trisna Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
Management of traditional villages by local communities (community based tourism) is the most important element because the community can become a driving force if it is managed and developed through the concept of tourism. The lack of variety in tourist activities in traditional villages and the activities that can be done are relatively the same, causing tourists who visit to feel bored and bored. Qualitative research was used in this study to describe factually, systematically and in detail regarding the management of community-based traditional villages in Sijunjung Regency (CBT). Data was collected using observation techniques, interviews, using 5 informants and documentation. Data was obtained from primary data in the form of the number of tourist visits to traditional villages, secondary data in the form of the organizational structure of traditional village management, and other documents. Based on the research results, it is stated that the management of traditional villages uses 4 basic management functions, namely Planning, Organizing, Actuating and Controlling.